PERGULATAN PEMIKIRAN PARADIGMA EKONOMI KERAKYATAN DALAM ARUS GLOBALISASI - Djakaria Machmud (Fakultas Hukum Universitas Swadaya Gunung Jati, 2011)
The conditionof the worldthat massively changed dan developed makesthechangesin thestructure,norms, andother fieldsof economy, social, politic and culture. Commitment toeconomicactivity and to the expected economicsystembecomes abigbetin the face ofglobal economic developmentbecause withoutrealizing it,the era ofglobalizationcausesa shift invalues.The biggest challengefaced inthis conditionis howthenSystemof populist Economicat the level ofPancasilaeconomic systembased onPancasilaMoralEconomycansurvive, evenhopefully itmaybethe best alternativetoget around theliberalizationof trade andcapitalism, so thatthrough theEconomicSystem ofPancasilawe adhere, it can beable to welfare all peoplewithout any exception.Key Word : PopulistEconomicSystems, PancasilaMoralEconomy, Welfare